Metropolis on the Styx : the underworlds of modern urban culture, 1800-2001 - Pike, David L. (David Lawrence), 1963- (Cornell University Press, 2007)
In Metropolis on the Styx, David L. Pike considers how underground spaces and their many myths have organized ways of seeing, thinking about, and living in the modern city. Expanding on the cultural history of underground construction in his acclaimed previous book, Subterranean Cities, Pike details the emergence of a vertical city in the imagination of nineteenth-century Paris and London, a city overseen by hosts of devils and undermined by subterranean villains, a city whose ground level was replete with passages between above and below. Metropolis on the Styx brings together a rich variety of visual and written sources ranging from pulp mysteries and movie serials to the poetry of Charles Baudelaire and the novels of Marcel Proust, F. Scott Fitzgerald, and Elinor Glyn to the broadsheets and ephemera of everyday urban life. From these materials, Pike conjures a working theory of modern underground space that explains why our notions about urban environments remain essentially nineteenth-century in character, even though cities themselves have since changed almost beyond recognition. Highly original in subject matter, methodology, and conclusions, Metropolis on the Styx synthesizes a number of critical approaches, periods of study, and disciplines in the analysis of a single category of space-the underground. Pike studies the built environments and the textual and visual ephemera (including little-known or unknown archival material) of Paris, London, and other cities in conjunction with canonical modern literature and art. This book integrates a rich visual component-photographs, movie stills, prints, engravings, paintings, cartoons, maps, and drawings of actual and imagined subterranean spaces-into the fabric of the argument.